North Actually: The Meaning of Place in Åsa Larsson’s Crime Novels About Rebecka Martinsson - Gregersdotter, Katarina (Journal of Northern Studies, 2021)
The article discusses and examines Larsson’s thus far five crime fiction novels to investigate how the formation of identity are connected to the peripheral North—the “real” North of the globally popular crime fiction subgenre Nordic Noir. Certain key concepts will be used to examine the novels: hyperlocalisation, neo-romanticism, anthropomorphism, borders, and history. This article will argue that in Åsa Larsson’s novels, place and its nature, borders and history are crucial in identity formation, and the place with its nature, climate and animals is an active agent in all the narratives.